2019
DOI: 10.14302/issn.2379-7835.ijn-19-2845
|View full text |Cite
|
Sign up to set email alerts
|

Structure Activity Relationship of Xanthones for Inhibition of Cyclin Dependent Kinase 4 from Mangosteen (Garcinia Mangostana L.

Abstract: The mangosteen fruit is a popular Southeast Asian fruit consumed for centuries. There have been a variety of xanthones isolated from the fruit, bark, roots and leaves with each having unique chemical and physical properties. Previously, the most abundant xanthone α-mangostin has been shown to inhibit CDK4. Herein we describe the role of selected xanthones from the mangosteen inhibiting CDK4. The evidence we provide here is that key functional groups are required to inhibit the CDK4 protein to prevent the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Mangosteen xanthones, especially MAG and GA, have been proven to display significant chemo-preventive and anticancer properties against numerous tumor types [12,[15][16][17][25][26][27]. Moreover, chemical modification of the xanthone structure is believed to further increase the anticancer properties, as described in [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Mangosteen xanthones, especially MAG and GA, have been proven to display significant chemo-preventive and anticancer properties against numerous tumor types [12,[15][16][17][25][26][27]. Moreover, chemical modification of the xanthone structure is believed to further increase the anticancer properties, as described in [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies on Garcinia mangostana, so far, researchers have found at least 80 types of xanthone compounds in various parts of the plant (Vemu, Nauman, Veenstra, & Johnson, 2019). Mangosteen pericarp has been proven by Ibrahim et al (2016) and another study of Mamat, Azizan, Baharum, Mohd Noor, and Mohd Aizat (2018) to contain high content of secondary metabolites such as xanthones, flavonoids, triterpenes and benzophenones (Ibrahim et al, 2016;Mamat et al, 2018).…”
Section: Sciex Internal Databasementioning
confidence: 99%
“…Thus, it was suggested that the use of antioxidants are ideal to treat this inflammatory disorder (Pleguezuelos-Villa et al, 2019). As a rich source of natural antioxidants and anti-inflammatory compounds, all parts of the xanthone-rich G. mangostana L. plant were traditionally consumed and utilized for the treatment of psoriasis (Ibrahim et al, 2018a;Ibrahim et al, 2018b;Vemu et al, 2019).…”
Section: Psoriasismentioning
confidence: 99%